Obstructive Sleep Apnea Syndrome dan Penderita Obesitas - Olivia Putri Chairunnisa; Mutiara Khalish; Achmad Gozali (CV. Jasa Sukses Abadi, 2022)
Obstructive sleep apnea (OSA) is characterized by episodes of respiratory arrest or shallow breathing during sleep. These episodes are caused by complete or partial collapse of the upper airway. Most of the time, respiratory events are associated with snoring, oxygen desaturation and decreased sleep duration. Obesity is an important risk factor for the development of OSA and is unique among the major preventable and modifiable risk factors. Many studies have evaluated the effect of weight loss, achieved by behavioral, pharmacological, and surgical approaches, in the management of OSA in obese patients. Initial management includes weight loss, which must be maintained in the long term to prevent relapse, and a 'weight loss program' is mandatory for patients. The success of such programs is usually influenced by the motivation of individuals and their support groups. The increasing prevalence of obesity has led to an increased incidence of respiratory distress during sleep. Obesity is associated with anatomical changes that predispose to upper airway obstruction during sleep. There are several mechanisms by which obesity can cause OSA, and the mechanisms are synergistic. Research shows that increased peripharyngeal fat deposition produces a mechanical load that offsets the maintenance of airway patency by dilator muscles and that this increase in collapsibility is particularly pronounced during sleep when there is decreased neuromuscular activity. In addition, there is some evidence to suggest that central obesity in particular may have a detrimental effect on neuromuscular activity in the upper airway. This literature review discusses the possible mechanisms of obstructive sleep apnea syndrome and the implications of the management that can be recommended to patients.